2017
DOI: 10.4174/astr.2017.93.4.209
|View full text |Cite
|
Sign up to set email alerts
|

The optimal duration of ischemic preconditioning for renal ischemia-reperfusion injury in mice

Abstract: PurposeThe aim of the present study was to investigate the protective effects of ischemic preconditioning for different periods of time and to elucidate the optimal safe ischemic preconditioning time for renal ischemia-reperfusion (I/R) injury in mice.MethodsA total of 25 male C57BL/6 mice were randomly divided into 5 groups (sham, I/R, ischemic preconditioning [IP]-3, IP-5, and IP-7 groups), in which the kidney was preconditioned with IP of various durations and then subjected to I/R injury (the last 3 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…The sevoflurane APC effect on mice kidneys was also reported in vivo (13). As far as is known, although the efficacy of renal IPC has not yet been shown to be clinically significant, unlike remote IPC for the kidney, renal IPc in mice reportedly suppresses the cell-death caused by subsequent IRI (8,9).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…The sevoflurane APC effect on mice kidneys was also reported in vivo (13). As far as is known, although the efficacy of renal IPC has not yet been shown to be clinically significant, unlike remote IPC for the kidney, renal IPc in mice reportedly suppresses the cell-death caused by subsequent IRI (8,9).…”
Section: Discussionmentioning
confidence: 87%
“…Alleviation of IRI improves the prognosis of the preserved kidney (7). Previous animal studies reported that ischemic preconditioning (IPc) alleviates renal IRI (8,9) and numerous clinical studies have elucidated the IPc effects on the kidney. Furthermore, these surgeries are performed under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…During the inflammatory reaction, pro-inflammatory factors, including IL-6 and IL-1β, were released, and the level of anti-inflammatory cytokines (IL-10 and IL-1Ra) was decreased (53). Previous studies have indicated that IPreC markedly suppressed the gene expression level of pro-inflammatory factors (TNF-α, IL-1β, and IL-6) and chemokines in patients with renal IR injury (54). In addition, IPreC inhibited the release of IL-1β and enhanced the generation of IL-10 following IR in normal and steatotic livers (55).…”
Section: Discussionmentioning
confidence: 99%
“…Renal ischemia/reperfusion (RIR) injury is a complex phenomenon, which disturbs renal function and induces kidney tissue damages (1, 2) resulting in acute kidney injury (AKI) (3). Clinically, RIR injury is occurred in different circumstances such as renal transplantation, renal surgeries, post-resuscitation shock, complex cardiovascular surgeries, and chemical agents/drugs induced renal toxicity (4, 5).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, RIR injury is occurred in different circumstances such as renal transplantation, renal surgeries, post-resuscitation shock, complex cardiovascular surgeries, and chemical agents/drugs induced renal toxicity (4, 5). Renal transplantation induced RIR injury increases renal dysfunction and mortality rate (3, 5). In general, ischemia followed by reperfusion induces reactive oxygen species (ROS) formation and inflammation, oxidative stress, mitochondrial damage, and apoptosis, which all contribute to renal disorder (3, 4).…”
Section: Introductionmentioning
confidence: 99%